Професійне самовизначення як педагогічна категорія - Єлова, Тетяна; Yelova, T. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті описано історичний аспект сутності поняття професійного самовизначення особистості, підходи філософів, психологів та педагогів до процесу формування цього поняття в різні історичні періоди розвитку людства. На основі історичного аналізу професійне самовизначення розглядається як педагогічна категорія, котра характеризує взаємозв’язки та взаємозалежності між змістом професійного педагогічного знання (від визначення об’єкта до виділення педагогічних технологій) та характеристиками особистості, розвиток та прояв яких людиною засновується на інформаційно-насиченому педагогічному супроводі. Зроблено висновок, що інноваційність та недостатня теоретико-методологічна розробка нового підходу до професійного самовизначення особистості полягає в забезпеченні необхідного державі та суспільству результату на основі вибору особистістю інформації про той чи інший вид професійної діяльності. Отже, виникає необхідність побудови концепції, моделі та розробки програми соціально-педагогічного супроводу особистості в системний процес її професійного самовизначення. Starting with initial stages of incipience of society, its structures and, as a consequence, ordered system of social and economical relations, the humanity realized the necessity of self- realizationin certain sphere of activity. It is manifested as the base of self-determination of personality. That is why the socially and pedagogically caused problem of professional self-determination of personality appears. The historical aspects of the essence of the concept of professional self-determination of personality, the approaches of philosophers, psychologists and pedagogues to the process of forming of this concept in different historical periods of development of humanity are described in the article. The professional self-determination as the pedagogical category is determined as the scientific concept of pedagogy, which expresses the most general properties and the interconnection of self-determination of personality with its development. The professional self-determination of personality in modern pedagogical science is determined from different points of view as the ability, capability and readiness of the person to build ones own life according to ones individuality; as the ability for self-regulation and as the way of interaction between personality and society. On the basis of historical analysis the professional self-determination is considered as the pedagogical category, which characterizes the relationships and interdependences between content of pedagogical professional knowledge (from the determination of the object to the allotment of the pedagogical technology) and features of the personality, the development and manifestation by person of which is based on the informative saturated support. There is made the conclusion, that innovative character and insufficient theoretical methodological elaboration of new approach to the professional self-determination of personality lies in the providing of needed by state and society result on the base of choice of personality of information about one or another kind of professional activity. So, there is the necessity to build the concept, model and elaboration of the program of social pedagogical support of the personality to the system process of ones professional self-determination.
The professional self-determination as the pedagogical category
Keywords: професійне самовизначення; professional self-determination; професійне знання; характеристики особистості; professional knowledge; personality characteristics